Presidential and Congressional Elections in Chile, December 2009 and January 2010 - Passarelli, Gianluca (European Review of Latin American and Caribbean Studies, 2011)
Sebastián Piñera’s presidential victory marks the end of the institutional transition process that began in 1989, and the electoral alternation clearly demonstrates that the Chilean democracy has matured. Nevertheless, some systematic problems still persist, for example the term limits on incumbent presidents from seeking another term arguably deprives citizens the right to re-elect an esteemed president. Moreover, the presidential and congressional majorities from different coalitions remain the distinctive feature of Chilean political and institutional system. The binominal electoral system significantly reduces the possibility of minor parties to be represented in Parliament, yet at the same time, the bipolar system is greatly weakened by intra-coalition fragmentation (because coalitions allow minor parties the possibility to overcome voting thresholds and get representation in parliament). At the institutional level the relationship between the executive and the legislature causes the president to confront the parties. The struggle between these actors could produce a stalemate. The article analyses the 2010 presidential and congressional elections, and furnishes many elements to enlighten the functioning of a distinctive party system, which operates through a unique electoral system in a highly centralized institutional framework. Resumen: Elecciones presidenciales y parlamentarias en Chile, diciembre de 2009 y enero de 2010La victoria de Sebastián Piñera marca definitivamente el fin del proceso de transición institucional comenzado en 1989, mientras que la alternancia electoral muestra la madurez de la democracia chilena. Sin embargo, persisten algunos problemas en el sistema. Por ejemplo, el límite impuesto a la re-elección del presidente en ejercicio priva a los electores del derecho a reelegir a un presidente estimado. Además, las mayorías presidenciales y parlamentarias formadas por distintas coaliciones, constituyen el rasgo distintivo del sistema político e institucional chileno. Pero el sistema electoral binominal reduce significativamente la posibilidad de los partidos menores de estar representados en el Congreso. Al mismo tiempo, el sistema bipolar está fuertemente debilitado por la fragmentación dentro de las coaliciones (que son las que permiten a los partidos más chicos superar el umbral de votos necesarios para llevar representantes al Congreso). A nivel institucional, las relaciones del poder ejecutivo con la legislatura llevan al enfrentamiento del presidente con los partidos. La lucha entre estos actores puede producir una situación de ‘tablas’, de estancamiento. En el artículo se analizan las elecciones presidenciales y parlamentarias del 2010 y se ofrecen elementos para explicar el funcionamiento del peculiar sistema de partidos chileno, el cual opera a través de un único sistema electoral en el marco de una estructura institucional altamente centralizada.